Analisis Pendapatan Nelayan Tangkap (Studi Kasus Di Rw 02 Kelurahan Sumber Jaya Kecamatan Kampung Melayu Kota Bengkulu) - Heni Sagita; As’ad Hasan; Ariel Siswantoro (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study aims to determine the income level of capture fishermen and analyze the factors that affect the income of capture fishermen in RW 02 Sumber Jaya Village, Kampung Melayu District, Bengkulu City. Capture fishermen are one of the coastal community groups that are highly dependent on marine products as the main source of income. However, fishermen's income often fluctuates because it is influenced by various factors such as production output, operational costs, number of workers, distance traveled to sea, and business ownership status. The research method used is qualitative descriptive. The population in this study amounted to 200 fishermen with a sample of 20 respondents selected using the proportionate stratified random sampling technique. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation. Data analysis uses the income formula Y = TR – TC, where TR is the total revenue and TC is the total cost. The results of the study show that the average fishermen's production is 4,813 kg per month with an average total revenue of IDR 28,875,000 and an average total cost of IDR 22,642,500 per month. The average net income of fishermen is IDR 6,232,500 per month. Factors that affect fishermen's income include catch production, operational costs, labor, distance to sea, and business ownership status. The higher the production output, the fishermen's income tends to increase, while high operational costs can reduce fishermen's net income.